2010
DOI: 10.3988/jcn.2010.6.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Suicidal Ideation in People with Epilepsy Living in Korea

Abstract: Background and PurposeThe risk of suicide or suicide attempts is reported higher in people with epilepsy (PWE) than in the general population. Although epileptic, psychiatric, and psychosocial factors are known risk factors for suicide or suicide attempt, no studies have evaluated the predictors of the severity of suicidal ideation-which is a warning sign for suicide attempts-in PWE. Therefore, we measured the severity of suicidal ideation and its risk factors.MethodsConsecutive PWE who were medicated with ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 24 publications
6
27
0
3
Order By: Relevance
“…In a multicenter study conducted in tertiary outpatient epilepsy centers associated with five universities in the US, the rate of current suicidal ideation was 12.2% and was associated with depression and anxiety [19]. Major risk factors for suicidal ideation were depression and other psychiatric symptoms rather than seizure-related variables [43]. We also found that suicidal ideation was more frequent among PWE with depressive and/or anxiety symptoms than among those without these symptoms.…”
Section: Discussionmentioning
confidence: 92%
“…In a multicenter study conducted in tertiary outpatient epilepsy centers associated with five universities in the US, the rate of current suicidal ideation was 12.2% and was associated with depression and anxiety [19]. Major risk factors for suicidal ideation were depression and other psychiatric symptoms rather than seizure-related variables [43]. We also found that suicidal ideation was more frequent among PWE with depressive and/or anxiety symptoms than among those without these symptoms.…”
Section: Discussionmentioning
confidence: 92%
“…Sleep disturbance has also been reported as an important predictor of passive suicidal ideation in the psychiatric literature 22,23 . The presence of anxiety and depression was a risk factor for the occurrence of suicidal ideation among the studied patients, and has been found in several studies 1,2,3,6,7,8,9 . The "suicidal ideators" had the worst rates for quality of sleep (PSQI), sleep alterations (PSQI), global score (PSQI), anxiety (BAI), and depression (BDI), which allows us to suggest a strong association between anxiety and depression and sleep.…”
Section: Discussionmentioning
confidence: 98%
“…We must be cautious in the study of comorbidity. Prevalence rates of psychiatric comorbidities require more studies and more appropriate therapeutic 1,2,3,4,5,6,7,8,9 . However, knowledge concerning suicide and its ideation in PWE is still limited.…”
mentioning
confidence: 99%
“…Another relation between suicide attempt, BD and abnormal EEG findings may be established through childhood traumas. In many studies, suicide attempt occurs at higher rates in bipolar cases with childhood trauma (Lim, Song, Hwang, Lee, Suh, Park, & Kwon, 2010). Drawing upon these findings, it can be suggested that in psychiatric disorders in general and in BPD in particular, the mediator between suicide and epilepsy is childhood trauma.…”
Section: Discussionmentioning
confidence: 99%